Role of anti-nucleosome antibodies in the diagnosis of systemic lupus erythematosus and as a marker for lupus nephropathy - Abdel Gawad, Eman R; Mansour, Amira I; Abdel Aziz, Yasser A; Soliman, Aml F; Fawzy, Rasha M (The Egyptian journal of immunology, 2014)
SLE is a heterogeneous disease, characterized by variation in clinical and serological manifestations. This study intended to verify the role of anti-nucleosome (anti-NCS) antibodies in diagnosis of SLE and lupus nephritis and to establish the correlation between antibody reactivity and disease activity. Study subjects included 35 patients diagnosed as SLE and two control groups. While the first is a group with other collagen diseases (n = 80), the second included 50 matched apparently healthy subjects. Serum IgG anti-NCS antibodies in all subjects were detected by ELISA. Serum anti-NCS were higher in SLE than in the two control groups (P < 0.001). Serum anti-NCS antibody levels were higher in SLE patients with renal affection (P < 0.001), malar rash and with hematological disorders (P < 0.05). Anti-NCS antibodies showed a higher diagnostic sensitivity (74.7%) and specificity (96%) than anti-dsDNA. Combining data of anti-NCS and anti-dsDNA antibodies increased the diagnostic specificity to 97.3%. In conclusion, serum anti-NCS antibodies have diagnostic value and play role in the assessment of disease activity especially active renal disease and may predict disease outcome.